ОРГАНІЗАЦІЯ РИБАЛЬСТВА У НИЖНЬОМУ ДНІСТРІ І ДНІСТРОВСЬКОМУ ЛИМАНІ (АНАЛІТИЧНИЙ ОГЛЯД) - Бушуєв, С.Г.; Снігірьов, С.М. (Marine Ecological Journal, 2023)
According to official statistics, the long-term dynamics of catch of the main commercial fish species and invertebrates of the Lower Dniester, changes in the structure and variations in the volume of catches are shown. Fisheries in the lower Dniester basin are characterized by a very high level of exploitation of aquatic bioresources, which, along with other factors of anthropogenic impact, has led to changes in the structure of ichthyocenosis. The rapid increase in the number of prussian carp in the last five years indicates a significant imbalance of the ecosystem. Modern approaches to the organization and regulation of fisheries, including commercial, amateur, in the waters of the NRF are considered.The current regulatory documents governing the organization and regulation of fisheries are analyzed. The predominance of IUU fishing over the legal forms of fisheries activities was noted, which seriously threatens the state of commercial aquatic bioresources and makes their rational sustainable use impossible. The problem of reliability of statistical data on the catch volumes of aquatic biological resources is noted. Official fishery statistics provide not only significantly reduced catches but also a distorted catch structure. There are practically no reliable data on fishing by amateur fishermen. The low efficiency of measures taken for the artificial reproduction of aquatic biological resources is shown. The most promising route is the restoration of natural spawning areas downstream of the river and in the estuary, which can have a greater environmental and economic impact than artificial reproduction. Proposals to improve the protection and rational use of aquatic bioresources in the Dniester basin were considered.